Dissolved organic carbon content and characteristics in relation to carbon dioxide partial pressure across Poyang Lake wetlands and adjacent aquatic systems in the Changjiang basin. (December 2016) - Wang, Huaxin; Jiao, Ruyuan; Wang, Fang; Zhang, Lu; Yan, Weijin
Abstract: Dissolved organic carbon (DOC) plays diverse roles in carbon biogeochemical cycles. Here, we explored the link between DOC and p CO2 using high-performance size-exclusion chromatography (HPSEC) with UV254 detection and excitation emission matrix (EEM) fluorescence spectroscopy to determine the molecular weight distribution (MW) and the spectral characteristics of DOC, respectively. The relationship between DOC and p CO2 was investigated in the Poyang Lake wetlands and their adjacent aquatic systems. The results indicated significant spatial variation in the DOC concentrations, MW distributions, and p CO2 . The DOC concentration was higher in the wetlands than in the rivers and lakes. p CO2 was high in wetlands in which the dominant vegetation was Phragmites australis, whereas it was low in wetlands in which Carex tristachya was the dominant species. DOC was divided into five fractions according to MW, as follows: super-low MW (SLMW, <1 kDa); low MW (LMW, 1–2.5 kDa); intermediate MW (IMW, 2.5–3.5 kDa); high MW (HMW, 3.5–6 kDa); and super-high MW (SMW, > 40 kDa). Rivers contained high proportions of HMW and extremely low amounts of SLMW, whereas wetlands had relatively high proportions of SLMW. The proportion of SMW (SMWp ) was particularly high in wetlands. We found that p CO2 significantly positively correlated with the proportion of IMW, and significantly negatively correlated with SMWp . These data improve our understanding of the MW of bioavailableDOC and its conversion to CO2 . The present results demonstrate that both the content and characteristics of DOC significantly affect p CO2 . p CO2 and DOC must be studied further to help understanding the role of the wetland on the regional CO2 budget. Highlights: The molecular weight of DOC showed spatial variations across the lake systems. p CO2 was related to the proportion of intermediate-molecular-weight DOC. p CO2 was negatively related to the proportion of super high molecular weight of DOC. Abstract : The molecular weight of DOC showed spatial variations across the Poyang Lake aquatic systems. p CO2 was related to the proportion of intermediate-molecular-weight DOC.